Kebutuhan transformasi bank digital Indonesia di era revolusi industri 4.0 - Suharbi, Muhammad Akbar; Margono, Hendro (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The occurrence of the Covid-19 pandemic forced humans to adapt to technology, not least in terms of finance, namely transactions in banking. This study aims to analyze the transformation of the banking industry into a digital bank in providing services to customers. This research is a type of qualitative research using secondary data from reliable literacy. The results of this study indicate that the transformation into a digital bank provides many advantages for banks to be able to continue to survive in running their business. Where digital banks are the choice of customers in transacting in the financial sector because it is easy, fast, and efficient. Transforming into a digital bank can also increase more customers and fee base income for banks because they can collaborate with fintech and e-commerce and can be efficient in managing bank assets which in turn can increase bank profits exponentially. However, in transforming into a digital bank, banks must have a strong foundation, especially in terms of infrastructure and security of customer data that is vulnerable to hacking attacks (cyber crime). So that in the Industrial Revolution 4.0 era technology is the main key in winning the competition and remaining sustainable in running a business, for that the banking sector in Indonesia is required to continue to innovate in providing the best service to its customers.